Analisa Faktor-faktor yang Berhubungan Terhadap Pemanfaatan Pelayanan Balai Laboratorium Kesehatan Semarang 2003 - Sriatmi, Ayun; Karyono, Karyono; Kunsianah, Kunsianah (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : Exploiting of service of health can be caused by need factor, factor of predisposing, situation of culture demography factor and enabling factor that are reachability, expense and price, time and distance, and also perception to quality of service. This research aim to know factors that having an effect on to exploiting of service of Laboratory Hall Health of Semarang.Method : The type of this research is Explanatory Research that is explaining relation between independent variable and dependent variable through examination of hypothesizing using cross sectional study method. Research population is patien visitor of Laboratory Hall Health counted 1.032 with 90 people of sample. Independent variable are age, work, level of education, and perception of dimention quality containing : directevidence, understanding, reability, wmphathy, and service. Dpeendent Variable is exploiting of service. Data analyse with Chi Square statistical test and logistics regression.Result : The result of research show there is no significant relation between age and exploiting of service. There is a relation between level of educatin and exploiting of service (p=0,009), work and exploiting of service (p=0,015), income and axploiting of service (p=0,012), perception and exploiting of service (p=0,002). Using Backward Conditional Method the result can be obtained that all independent variable is tested together using logistics regression method yielding three variables show the influence to exploiting of service : perception (p=0,002), level of education (p=0,016). The most dominant variable in giving influence to exploiting of service is perception. Third of the variable with goodperception category (1), education more than 9 years (1), and income more or equal to UMK (1), ence possibility exploit service obtained equal to 86,6%.Keywodrs: exploiting of service, laboratory hall health, perception.